Numerická analýza dotvarování betonu - Dajčar, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Bakalářská práce se zabývá výpočtem dvou významných reologických jevů, a to dotvarováním a relaxací. V úvodu je popsána podstata těchto jevů a způsob, jakým lze chování materiálu popsat pomocí reologických modelů, konkrétně Kelvinova a Maxwellova modelu. Analýza dotvarování je provedena integrálním a diferenciálním přístupem pro nestárnoucí i stárnoucí materiál. Výpočet relaxace je proveden pro nestárnoucí materiál. V případě integrálního přístupu jsou v textu popsány a porovnány tři integrační metody. K řešení diferenciálním přístupem jsou využity reologické řetězce, Kelvinův pro dotvarování a Maxwellův pro relaxaci. Je rovněž představen postup hledání vhodných parametrů reologických řetězců. Na závěr jsou oba přístupy výpočtu porovnány a shrnuty jejich výhody a nevýhody.

The bachelor’s thesis focuses on the calculation of two significant rheological phenomena, namely creep and relaxation. The introduction describes the fundamental nature of these phenomena and the way in which material behaviour can be described using rheological models, specifically the Kelvin and Maxwell model. Creep analysis is carried out using integral and differential approach for non-aging and aging material. Relaxation is analysed for a non-aging material. In case of the integral approach, three integration methods are described and compared. In the differential approach, rheological chains are employed, the Kelvin chain for creep and the Maxwell chain for relaxation. The thesis also presents the procedure for determining suitable parameters of the rheological chains. In conclusion, both computational approaches are compared, and their advantages and disadvantages are discussed.
Numerical Analysis of Creep in Concrete
Keywords: dotvarování; relaxace; Kelvinův model; Maxwellův model; materiálový bod; integrální přístup; diferenciální přístup; hledání parametrů; Kelvinův řetězec; Maxwellův řetězec; creep; relaxation; Kelvin model; Maxwell model; material point; integral approach; differential approach; parameter identification; Kelvin chain; Maxwell chain